2017
DOI: 10.1093/jb/mvw102
|View full text |Cite
|
Sign up to set email alerts
|

PRMT2 interacts with splicing factors and regulates the alternative splicing of BCL-X

Abstract: Protein arginine N-methyltransferase 2 (PRMT2) functions in JAK-STAT and Wnt/β-catenin signalling pathways, serves as a nuclear receptor-dependent transcriptional co-activator, and represses NF-κB and E2F1 transcription factor activities to promote apoptosis. We have previously demonstrated that PRMT2 interacts with PRMT1 and increases its activity. Here, we reveal associations using proteomics between the PRMT2 SH3 domain and splicing factors including Src-associated in mitosis 68 kDa protein (SAM68), a PRMT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 44 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…However, PRMT2 is known to promote apoptosis via NF-κB dependent mechanism in which NF-κB transcription is inhibited, preventing IκB-α from leaving the nucleus, resulting in increased levels of nuclear IκB-α and decreased NF-κB binding to DNA [ 40 ]. PRMT2 is known to interact with a multitude of splicing factors and splicing-related proteins, and other interactions are possible [ 41 ]. Hou et al revealed a role for PRMT2 in dendrite arborization by promoting methylation of the actin nucleator, Cobl [ 42 ].…”
Section: Functional Significance Of Arginine Methylationmentioning
confidence: 99%
“…However, PRMT2 is known to promote apoptosis via NF-κB dependent mechanism in which NF-κB transcription is inhibited, preventing IκB-α from leaving the nucleus, resulting in increased levels of nuclear IκB-α and decreased NF-κB binding to DNA [ 40 ]. PRMT2 is known to interact with a multitude of splicing factors and splicing-related proteins, and other interactions are possible [ 41 ]. Hou et al revealed a role for PRMT2 in dendrite arborization by promoting methylation of the actin nucleator, Cobl [ 42 ].…”
Section: Functional Significance Of Arginine Methylationmentioning
confidence: 99%
“…For example, the Bcl-x gene can generate two isoforms as a result of alternative splicing. The short protein Bcl-xS is pro-apoptotic, while the large protein Bcl-xL is anti-apoptotic ( 21 ).The alternative splicing of Bcl-x can be regulated by both protein arginine methyltransferase 2 (PRMT2) and polypyrimidine tract-binding protein 1 (PTBP1) ( 19 , 208 ). In the failing heart, the expression of Bcl-xL mRNA is significantly increased after ventricular assist device implantation ( 14 ).…”
Section: Functional Impact Of Alternative Mrna Splicing In Heartmentioning
confidence: 99%
“…Serine–arginine rich (SR) splicing factors are another prominent splicing factor family [ 166 ] and it should come as no surprise that SR splicing factors are methylated due to the abundance of arginine residues they contain. The SR protein SF2A-p32 associates with PRMT1 and PRMT5 [ 167 ], while PRMT2 associates with multiple SR proteins and hnRNPs, including Sam68, to regulate alternative splicing of the mitochondrial protein Bcl-x [ 168 ]. Arginine methylation of Sam68 by PRMT1 localizes it to the cytoplasm [ 169 ] and reduces its RNA binding ability [ 170 ], thus indicating that Sam68 is highly regulated by arginine methylation.…”
Section: Protein Arginine Methylationmentioning
confidence: 99%